Penambahan Halquinol dalam Pakan Buatan untuk Meningkatkan Pertumbuhan Benih Ikan Baung (Mystus nemurus) - Diana Rachmawati; Pinandoyo Pinandoyo; Anita Dwi Purwanti (Jurnal Perikanan Universitas Gadjah Mada, 2006)
This research aimed to determine effect of halquinol addition as feed additive in artificial feed of baung (Mystus nemurus) seed. Some factor measured as indicators of the effect were growth rate, feed conversion ratio (FCR), survival rate and optimum dose of halquinol which resulted the best growth, feed conversion ratio (FCR) and survival rate. Baung fish seed (0,83 g of mean body weight) were used in this experiment. The seed were obtained from Freshwater Aquaculture Center (BBAT), Sukabumi,West Java. The test feed was commercial artificial feed powder which was pelleted. This research used Completely Random Design with 4 treatments in triplicates. The treatments were addition of halquinol in the feed with different concentration i.e.: A (0 mg/kg), B (12.5 mg/kg), C (25 mg/kg) and D(37.5 mg/kg). The result indicated that addition of halquinol in feed increased the growth rate and decreased feed conversion ratio, but did not affect the survival rate of baung seed. Addition of halquinol at 25 mg/kg feed gave the highest growth rate and lowest FCR.